BERBAGAI BENTUK PENGAWASAN KEBIJAKAN DAERAH DALAM ERA OTONOMI LUAS - Enny Nurbaningsih (Fakultas Hukum Universitas Gadjah Mada, 2011)
Following the abolishment of all controlling measures except repressive control, decentralisation triggers fundamental changes in local government administration. Tight control may obstruct regions’ autonomy and hamper central-regional relation. Proportional control is indispensable for balancing out local governments’ freedom. All monitoring measures outside Act 32/2004 are unwarranted without improvement of legal instruments at central government.Dengan menghapuskan semua bentuk pengawasan kecuali pengawasan represif, desentralisasi menciptakan perubahan fundamental dalam penyelenggaraan pemerintahan daerah. Pengawasan yang ketat dapat mengekang daerah dan mengganggu hubungan pusat-daerah. Pengawasan otonomi yang proporsional diperlukan sebagai penyeimbang kebebasan pemerintahan daerah. Bentuk pengawasan di luar UU 32/2004 cenderung berlebihan tanpa perbaikan instrumen hukum tingkat pusat.